Resource mattress. The potential of refuse materials - Alexa Kreissl (Agathón)
Mattresses are multi-material products whose exact composition is mostly unknown to the waste collector, so they can hardly be recycled and continue to be incinerated. Valuable resources are lost and no longer returned to the material cycle. Foam re-use and mechanical recycling account for only a negligible share of the market. The research presented here explores the potential of re-using mattresses as thermal and acoustic insulation for construction projects and attempts to find re-purpose in order to reduce waste and emissions, save resources and provide the insulation needed. This specific case study serves as a method to identify and demonstrate the flow and potential on a much larger scale. Considering comparable and possibly compatible properties of different foams this study explores the possibility of using them in a larger format. The approach is based on an unbiased exploration of the material, which only as a second step uses scientific methods to measure the intuitive exploration of the properties.